Isolation and Characterization of Novel Chlorella Vulgaris Mutants With Low Chlorophyll and Improved Protein Contents for Food Applications - Schüler, Lisa; Greque de Morais, Etiele; Trovão, Mafalda; Machado, Adriana; Carvalho, Bernardo; Carneiro, Mariana; Maia, Inês; Soares, Maria; Duarte, Paulo; Barros, Ana; Pereira, Hugo; Silva, Joana; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
Microalgae are widely used as food supplements due to their high protein content, essential fatty acids and amino acids as well as carotenoids. The addition of microalgal biomass to food products (e.g., baked confectioneries) is a common strategy to attract novel consumers. However, organoleptic factors such as color, taste and smell can be decisive for the acceptability of foods supplemented with microalgae. The aim of this work was to develop chlorophyll-deficient mutants of Chlorella vulgaris by chemically induced random mutagenesis to obtain biomass with different pigmentations for nutritional applications. Using this strategy, two C. vulgaris mutants with yellow (MT01) and white (MT02) color were successfully isolated, scaled up and characterized. The changes in color of MT01 and MT02 mutant strains were due to an 80% and 99% decrease in their chlorophyll contents, respectively, as compared to the original wild type (WT) strain. Under heterotrophic growth, MT01 showed a growth performance similar to that of the WT, reaching a concentration of 6.06 and 5.84 g L-1, respectively, whereas MT02 displayed slightly lower growth (4.59 g L-1). When grown under a light intensity of 100 µmol m-2 s-1, the pigment content in MT01 increased without compromising growth, while MT02 was not able to grow under this light intensity, a strong indication that it became light-sensitive. The yellow color of MT01 in the dark was mainly due to the presence of the xanthophyll lutein. On the other hand, phytoene was the only carotenoid detected in MT02, which is known to be colorless. Concomitantly, MT02 showed the highest protein levels, reaching 48.7% of DW, a 60% increase as compared to those of the WT. MT01 exhibited a 30% increase in protein content when compared to that of the WT, reaching a protein content of 39.5% of DW. Taken together, the results strongly suggest that the partial abrogation of pigment biosynthesis is a factor that might promote higher protein contents in this species. Moreover, because of their higher protein and lower chlorophyll contents, the MT01 and MT02 strains are likely candidates to be feedstocks for the development of novel, innovative foods and food supplements.